2020
DOI: 10.1111/emre.12416
|View full text |Cite
|
Sign up to set email alerts
|

The Role of pro‐Social Orientation and National Context in Corporate Environmental Disclosure

Abstract: Corporate environmental disclosure can be of strategic value for firms as they project their aspired image and seek to gain recognition and legitimacy. While the importance of environmental disclosure has been thoroughly documented and is understood, research has shed considerably less light on the forces that drive it. In this paper, we set out to explain what determines corporate environmental disclosure. In drawing upon the instrumental stakeholder theory in conjunction with institutional theory, we hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 92 publications
(190 reference statements)
0
9
0
Order By: Relevance
“…Institutional pressures, together with well-informed, proactive communicators, have a strong influence on organizations' decisions to engage in meaningful disclosure (Biswas et al, 2019;Bellamy et al, 2020). Thus, for institutional theory, disclosure is explained as a reaction to institutional and external pressures, given that these are both considered in the process of constructing social identity (Akbar and Deegan, 2021;Boura et al, 2020), as well as carried out to achieve internal legitimacy and compliance with formally institutionalized processes (Biswas et al, 2019;Oliveira et al, 2019).…”
Section: Origin Of Theories For Corporate Voluntary Disclosurementioning
confidence: 99%
See 1 more Smart Citation
“…Institutional pressures, together with well-informed, proactive communicators, have a strong influence on organizations' decisions to engage in meaningful disclosure (Biswas et al, 2019;Bellamy et al, 2020). Thus, for institutional theory, disclosure is explained as a reaction to institutional and external pressures, given that these are both considered in the process of constructing social identity (Akbar and Deegan, 2021;Boura et al, 2020), as well as carried out to achieve internal legitimacy and compliance with formally institutionalized processes (Biswas et al, 2019;Oliveira et al, 2019).…”
Section: Origin Of Theories For Corporate Voluntary Disclosurementioning
confidence: 99%
“…, 2020). Thus, for institutional theory, disclosure is explained as a reaction to institutional and external pressures, given that these are both considered in the process of constructing social identity (Akbar and Deegan, 2021; Boura et al. , 2020), as well as carried out to achieve internal legitimacy and compliance with formally institutionalized processes (Biswas et al.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The newly introduced concept can be beneficial in highlighting the heterogeneity across different organizations when it comes to climate change disclosure and addressing some conflicting findings stemming from the extant scholarship. Second, we gather evidence from different streams of literature, including sustainability reporting (Boura et al, 2020; Cabeza‐García et al, 2018), strategic leadership (Papagiannakis & Lioukas, 2018; Yamak et al, 2019), environmental management (Eiadat & Fernández Castro, 2018), and more, providing a holistic understanding of climate change disclosure. Third, although we find that the outcome dimension is less examined compared with the antecedent dimension, we highlight some critical gaps in both that suggest a future research agenda.…”
Section: Discussionmentioning
confidence: 99%
“…Narrative reporting has been the management’s most common communication channel with the stakeholders (Elmarzouky et al , 2021; Boura et al , 2020; Fisher et al , 2019). The central bank of England in 2017 reported that around 90% of the financial information was extracted from the narrative sections rather than the financial statements (Bank of England, 2015; Lewis and Young, 2019).…”
Section: Introductionmentioning
confidence: 99%